MAPPING OF ECOSYSTEM MANAGEMENT PROBLEMS IN GILI MENO, GILI AIR AND GILI TRAWANGAN (GILI MATRA) THROUGH PARTICIPATIVE APPROACH - I Wayan Suana; Hilman Ahyadi (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Coral reefs, mangroves and birds are becoming the major attraction of tourism in three islands - Gili Meno, Gili Air and Gili Trawangan (Gili Matra) - Lombok, Indonesia. Since the launching as a conservation area in 1993, tourism in Gili Matra has grown rapidly. On the other hand, the ecosystem continues to be degraded. Sooner or later, the ecosystem degradation will affect tourism and economic sustainability of the community in Gili Matra. The purposes of this study were to identify the stakeholders, and to map the ecosystem management problems in Gili Matra, to provide the basis for policy making in the future. The research method was depth interviews and focus group discussion (FGD). Identification of stakeholders was conducted using stakeholder analysis, while mapping of ecosystem management problems was carried out by participatory mapping. The stakeholders, who manage the ecosystem as tourism assets in Gili Matra, are: government, community and businessmen. The fishermen, tourists and businessmen are the primary stakeholders, meaning they have a high interest and the greatest influence on ecosystem management. Destructive behavior of stakeholders, especially the main stakeholders has led to the degradation of the ecosystem in Gili Matra, so it is important to nurture these stakeholders, to sustain tourism and economic viability of the community in Gili Matra.